Some Induced Aggregating Operators with Fuzzy Number Intuitionistic Fuzzy Information and their Applications to Group Decision Making - Guiwi Wei; Xiaofei Zhao; Rui Lin (International Journal of Computational Intelligence Systems, 2010)
With respect to multiple attribute group decision making (MAGDM) problems in which both the attribute weights and the expert weights take the form of real numbers, attribute values take the form of fuzzy number intuitionistic fuzzy numbers, a new group decision making analysis method is developed. Firstly, some operational laws of fuzzy number intuitionistic fuzzy numbers, score function and accuracy function of fuzzy number intuitionistic fuzzy numbers are introduced. Then a new aggregation operator called induced fuzzy number intuitionistic fuzzy ordered weighted geometric (I-FIFOWG) operator is proposed, and some desirable properties of the I-FIFOWG operators are studied, such as commutativity, idempotency and monotonicity. An I-FIFOWG and FIFWG (fuzzy number intuitionistic fuzzy weighted geometric) operators-based approach is developed to solve the MAGDM under the fuzzy number intuitionistic fuzzy environment. Furthermore, we propose the induced fuzzy number intuitionistic fuzzy ordered weighted averaging (I-FIFOWA) operator. Finally, an illustrative example is given to verify the developed approach and to demonstrate its practicality and effectiveness. Finally, an illustrative example is given to verify the developed approach.